PENERAPAN TEKNIK PROBING UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA MATERI KELARUTAN DAN HASIL KALI KELARUTAN DI SMAN 3 PEKANBARU - Atika Ramadani Atika Ramadani; Betty Holiwarni Betty Holiwarni; Sri Haryati Sri Haryati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : The research on application of probing technique has been done to improve of student achievement on the subject of solubility and solubility product in SMAN 3 Pekanbaru. Form of the research is experimental research with pretest-posttest design. The sample consist of two classes, namely class XI IPA 4 as the experimental and class XI IPA 5 as control class which randomly selected after had tested normality and homogeneity. Experiment class was given implementing probing technique while the control class was not given implementing probing technique. Data analysis technique used the t-test. Based on the result of the final data processing t-test formula obtained tarithmetic>ttable (5,64 > 1,67) means the application of probing technique can improve student achievement on the subject of solubility and solubility product in class SMAN 3 Pekanbaru, with category increased student achievement on experiment class including high with the normalized gain scores (N-gain) about 0,71. Key Words: Probing Technique, Learning achievement, Solubility and solubility product.